Proton conductivity in a copper(II) bipyridine glycoluril complex: the synergistic role of coordinated water and hydrogen-bonded networks - Khatavkar, Medhavi D.; Panday, Rishukumar; Singh, Mayank U.; Kurungot, Sreekumar; Kumbhar, Avinash S. (Inorganica Chimica Acta, 2026)
A dinuclear complex of copper(II) and bipyridine glycoluril (BPG) ligand is synthesized, characterized, and structurally examined by single-crystal X-ray diffraction. The complex [Cu2(BPG)2(NO3)2(H2O)4](NO3)2 center dot 5H2O (complex (1)) further forms a supramolecular network sustained by H-bonds between NH/C=O of BPG, coordinated/free water molecules, and nitrate anions. The complex exhibits a proton conductivity of 5.99 x 10_ 3 S center dot cm_ 1 at 90 degrees C and 95 % relative humidity (RH) with activation energy value Ea 0.35 eV, suggesting the Grotthuss proton transport mechanism. This value is consistent with those reported for proton-conducting systems in which coordinated water molecules play a critical role in facilitating efficient proton hopping across hydrogen-bonded networks.
Keywords: Coordinated water; Copper(II) complex; H -bonding; proton conduction; Supramolecular networks